The research relationship: participant perspectives on consent in biobanking - Rachel Thompson; Kate Lyle; Gabrielle Samuel; Jo Holliday; Fenella Starkey; Susan Wallace; Anneke Lucassen (BMC Medical Ethics)
Abstract Background This paper examines challenges associated with the governance of large-scale biobanks. As the collection and interrogation of population-scale data is increasingly positioned as a route to new understandings of health and disease, large-scale biobanks are becoming essential elements of research infrastructure. However, their longitudinal nature presents challenges for governance, particularly in relation to consent. Typically, participants agree to specific activities at recruitment, but evolving technologies make it difficult to anticipate future research applications at this time. Using a case study from UK Biobank, we demonstrate how trying to reconcile new research activities with old consent risks overlooking critical ethical issues —particularly how the proposed activity aligns with participants’ understanding and expectation of biobank research. Methods We conducted focus groups with UK Biobank participants using individual and group exercises to explore their views on consent and different types of research on their samples and data. Results Our findings show that participants locate responsibility for research decisions with the biobank, rather than seeking control through their consent. They perceive their consent not as a one-off agreement but as the `opening act' for a research relationship with the biobank that can be continued through communication. Conclusions Focussing on the ongoing research relationship -and the practices that sustain it- is more important than the specific wording on consent forms signed at recruitment. We argue this will be more effective in meeting participant expectation as well as supporting ethical research.